Margherita Marchione as Antihero for Italian Jews: A Complex Message of Hope - Vitale, L. (A Century of Italian War Narratives: Voices from the Sidelines, 2023)
Lisa Vitale discusses the intellectual contribution of historian and apologist Margherita Marchione in redefining the role of Pius XII during the atrocities of the Nazi Holocaust by means of personal narratives of the Sisters of St Lucy Filippini (of which Marchione was a member) and the Jewish refugees they sheltered, including the prominent Roman Di Veroli family. The chapter paints a multi-faceted, and sometimes contradictory, picture of Catholic charity during those turbulent and confusing times. Despite Marchione’s defense of Vatican (in-)action during the mass extermination of the Jews, she brings a message of hope to today’s Jewish Italian citizens. © 2023 by Koninklijke Brill NV, Leiden, The Netherlands.
Keywords: dept.wll

Partisan Diary: Ada’s Wars - Palma, P. (A Century of Italian War Narratives: Voices from the Sidelines, 2023)
This chapter focuses on the figure of Ada Gobetti and her humble, yet crucial contribution, as a partisan collaborator and leader who helped dismantle the Nazi-Fascist political system in the aftermath of the 1943 Armistice. The author aims at shedding new light on Gobetti’s work that has long been ignored, highlighting how women regained visibility because of their role in support of the Resistance. © 2023 by Koninklijke Brill NV, Leiden, The Netherlands.
Keywords: dept.wll

Challenges and achievements of an online intercultural exchange in time of crisis - Fornara, F; Gleason, Jesse (How We Take Action: Social Justice in PK-16 Language Classrooms, 2023)
How We Take Action brings together practical examples of social justice in language education from a wide range of contexts. Many language teachers have a desire to teach in justice-oriented ways, but perhaps also feel frustration at how hard it is to teach in ways that we did not experience ourselves as learners and have not observed as colleagues. As a profession, we need more ideas, more examples, and wider networks of allies in this work. This book includes the work of 59 different authors including teachers and researchers at every level from Pre-K to postsecondary, representing different backgrounds, languages, and approaches to classroom practice. Organized into three sections, some of the chapters in this collection report on classroom research while others focus on key practices and experiences. Section I is entitled Inclusive and Empowering Classrooms. In this section authors take a critical approach to classroom practices by breaking with the status quo or creating spaces where students experience safety, access, and empowerment in language learning experiences. Section II, Integration of Critical Topics, addresses a variety of ways teachers can incorporate justice-oriented pedagogies in day-to-day instructional experiences. Social justice does not happen haphazardly; it requires careful, critical examination of instructional practices and intentional planning as instructors hope to enact change. Section III, Activism and Community Engagement, explores how teachers can empower students to become agents for positive change through the study of activism and constructive community engagement programs at local and global levels.
Keywords: dept.wll

A Century of Italian War Narratives: Voices from the Sidelines - Gussago, Luigi; Palma, Pina (Brill, 2023)
Keywords: Contemporary History; Criticism & Theory; Cultural History; History; Literary Relations; Literature and Cultural Studies; Memory Studies; dept.wll

The knowledge framework for building teacher awareness of language in content instruction - Schmitt, Elena; Gleason, Jesse (Social Practices in Higher Education; A Knowledge Framework Approach to Linguistic Research and Teaching; Slater, 2023)
Keywords: dept.wll

Bilingualism - Schmitt, Elena G. (Encyclopedia of Slavic Languages and Linguistics Online, 2023)
Keywords: dept.wll

Ecocritical Reflections on Fiction Written by Nobel Laureate Mario Vargas Llosa - Flores, W. (Humanidades, 2023)
This article examines anthropocentric and ecocentric tendencies in two major works written by Mario Vargas Llosa, The Storyteller and The Dream of the Celt, to identify the value of those novels in ecocritical terms. I provide this analysis in the context of recent academic dialogue which notes an apparent contradictory relationship between the presentation of abuses of Amazonian people and their environment, and the portrayal of Westernized protagonists as their saviors in fiction written by Vargas Llosa. This essay provides a solution to this paradox and other apparent contradictions in his narratives and posits that even though the anthropocentric literary discourse concerning the environment has declined throughout the latter part of the twentieth century, in part, due to the rise of the environmental movement, this type of discourse has changed in Vargas Llosa’s literature, rejecting early twentieth century misconceptions of the natural world but holding onto technocentric neoliberal beliefs. © 2023, University of Montevideo. All rights reserved.
0 citations (Crossref) [2023-10-31]
Keywords: Mario Vargas Llosa; Peruvian literature; The Dream of the Celt; The Storyteller; dept.wll; ecocriticism; environment; peer-reviewed

Coping with a language loss: A case of linguistic and cultural re-encoding of memories in language attriters - Sorokina, Anastasia (International Journal of Bilingualism, 2023)
Aims and objectives:This study investigates the effects of language loss on bilingual autobiographical memory. More specifically, the study focuses on whether severe language loss would lead to any linguistic changes and/or interfere with how memories are recalled and shared.Methodology:Autobiographical memories were elicited with the help of a cued-recall technique and memory questionnaire from two groups of immigrants?attriters (who experienced significant language loss) and bilinguals (who retained their first language proficiency).Data and analysis:The data set consisted of pre-immigration memories that were originally encoded in the first language, Russian. The frequency of recall (i.e., sharing memories with others as well as reminiscing) and linguistic components (i.e., words) of memories elicited from the attriters and bilinguals were analyzed quantitatively and qualitatively.Findings and conclusion:Overall, attriters were able to recall memories that were originally encoded in the forgotten language. They also reported reminiscing about their pre-immigration memories and sharing their memories with others. However, attriters revealed that the pre-immigration memories came to them with words in the second language, English, which was not the case with bilinguals. Attriters also reframed memories for several Russian culture-specific items and events. This finding is indicative of memory re-encoding?a phenomenon when memories are updated, stored, and subsequently retrieved with added information. While this finding points to the bilingual mind?s ability to adapt to language loss, it may also suggest linguistic and cultural assimilation under the influence of the new language and culture.Originality:This is the first investigation of autobiographical memory in bilinguals with severe language loss that highlights the malleability and adaptability of the bilingual mind as well as the importance of language maintenance.
0 citations (Crossref) [2023-10-31]
Keywords: dept.wll; peer-reviewed